Toll-Like Receptors and Relevant Emerging Therapeutics with Reference to Delivery Methods - Nasir Javaid; Farzana Yasmeen; Sangdun Choi (Pharmaceutics, 2019)
The built-in innate immunity in the human body combats various diseases and their causative agents. One of the components of this system is Toll-like receptors (TLRs), which recognize structurally conserved molecules derived from microbes and/or endogenous molecules. Nonetheless, under certain conditions, these TLRs become hypofunctional or hyperfunctional, thus leading to a disease-like condition because their normal activity is compromised. In this regard, various small-molecule drugs and recombinant therapeutic proteins have been developed to treat the relevant diseases, such as rheumatoid arthritis, psoriatic arthritis, Crohn’s disease, systemic lupus erythematosus, and allergy. Some drugs for these diseases have been clinically approved; however, their efficacy can be enhanced by conventional or targeted drug delivery systems. Certain delivery vehicles such as liposomes, hydrogels, nanoparticles, dendrimers, or cyclodextrins can be employed to enhance the targeted drug delivery. This review summarizes the TLR signaling pathway, associated diseases and their treatments, and the ways to efficiently deliver the drugs to a target site.